Efficacy of a topical formulation containing eprinomectin, esafoxolaner and praziquantel (NexGard® Combo) in the treatment of natural respiratory capillariosis of cats - Di Cesare Angela; Morganti Giulia; Vignoli Massimo; Colombo Mariasole; Veronesi Fabrizia; Bufalari Antonello; Tielemans Eric; Beugnet Frederic; Traversa Donato (Parasite, 2024)
Feline pulmonary capillariosis is a significant disorder due to its distribution and clinical impact. This study evaluated the safety and efficacy of two administrations 28 days apart of a topical solution containing esafoxolaner, eprinomectin and praziquantel (NexGard® Combo) in treating Eucoleus aerophilus (syn. Capillaria aerophila) infection in naturally infected cats. Cats were allocated to two groups: G1 cats (n = 23) received two treatments at study days (SDs) 0 and 28 (±2) and were evaluated for 6 weeks, and G2 cats (n = 17) served as a negative control for 6 weeks and were then treated twice on SDs 42 (±2) and 70 (±2), allowing for an additional 6-week assessment of efficacy. Each cat was subjected to McMaster coproscopy at SDs −7/0, 28 (±2) and 42 (±2) for both groups, 70 (±2) and 84 (±2) only for G2. Clinical examination and chest radiographic images were performed at SDs 0, 28 (±2) and 42 (±2) for G1 and G2, 70 (±2) and 84 (±2) only for G2. The comparison of EPG (eggs per gram of feces), clinical (CS), and radiographic scores (RS) at each time-point was used as a criterion. The efficacy based on the EPG reduction was 99.5% (G1) and 100% (G2) after two administrations of NexGard® Combo 2 weeks apart. At SD 0, no significant differences for CS and RS were recorded between G1 and G2, while a significant reduction (p < 0.05) was observed post-treatment for CS, RS, oculo-nasal discharge, auscultation noises, and cough. Two doses of NexGard® Combo 28 days apart stopped egg shedding and significantly improved clinical alterations in cats infected by E. aerophilus.